2014
DOI: 10.1371/journal.pone.0112803
|View full text |Cite
|
Sign up to set email alerts
|

Rare Detection of Occult Hepatitis B Virus Infection in Children of Mothers with Positive Hepatitis B Surface Antigen

Abstract: The prevalence of occult Hepatitis B virus (HBV) infection in children was considerably varied from 0.1–64% in different reports. In this study we aimed to investigate the prevalence of occult HBV infection among the children born to mothers with positive hepatitis B surface antigen (HBsAg) in Jiangsu, China. Serum samples were collected from 210 children of 207 mothers with positive HBsAg. HBV serological markers were detected by ELISA and HBV DNA was detected by nested PCR. Homology comparison of HBV sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…Comparing with previous studies, the prevalence of OBI babies born to HBsAg positive mothers was 42% in Indian babies age 6‐72 months, 28% in Iranian children age 10‐128 months, 0 or 4.9% in Chinese babies age 1‐51 months, respectively. Unfortunately, those studies did not compare babies OBI genotypes or sequences with their mothers.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Comparing with previous studies, the prevalence of OBI babies born to HBsAg positive mothers was 42% in Indian babies age 6‐72 months, 28% in Iranian children age 10‐128 months, 0 or 4.9% in Chinese babies age 1‐51 months, respectively. Unfortunately, those studies did not compare babies OBI genotypes or sequences with their mothers.…”
Section: Discussionmentioning
confidence: 48%
“…3,4 The outcome of hepatitis B vaccination plus specific immune globulin (HBIG) in newborns to HBsAg positive mothers has been previously described. 5,6 In recent years, occult hepatitis B virus infection (OBI) was defined as the presence of HBV DNA in serum and/or liver but the absence of Ethical approval: This study was approved by the Medical Ethics Committee of Nanfang hospital of Southern Medical University, Guangzhou, China. All participant mothers signed an informed consent for themselves and babies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 In real-life practice, imperceptible cross-contamination may sometimes occur in performing PCR. 3 Therefore, the diagnosis of OBI should be ascertained before studying the natural history of OBI. Otherwise, the results would be misleading.…”
Section: Occult Hepatitis B Virus Infection or Occult Crosscontaminamentioning
confidence: 99%
“…Whether these anti-HBc-positive children were also anti-HBs-positive is not known, as the authors did not mention this ; if positive, it should be nearly impossible to acquire a novel HBV infection except mutant virus. The authors used occult HBV infection (OBI) to explain the result (Shahmoradi et al, 2012), but OBI is extremely low in infants of HBsAg-positive mothers (Liu et al, 2014), and most of the reported OBI cases in vaccinated infants or children result from occult cross-contamination (Zhou, 2016). Actually, the same authors reported this high proportion of OBI in vaccinated children from the same area (Xu et al, 2010), but more than half of the OBI was caused by crosscontamination, as evidenced by 51.2% of isolates with an identical HBV sequence; this is impossible in different individuals except if they were infected with the same virus.…”
mentioning
confidence: 99%